The transition state in the folding-unfolding reaction of four species of three-disulfide variant of hen lysozyme: the role of each disulfide bridge - Yokota, Atsushi; Izutani, Kazuki; Takai, Masanori; Kubo, Yukiko; Noda, Yasuo; Koumoto, Yasuko; Tachibana, Hideki; Segawa, Shin-ichi (Journal of molecular biology, 2000)
The effects of lacking a specific disulfide bridge on the transition state in folding were examined in order to explore the folding-unfolding mechanism of lysozyme. Four species of three-disulfide variant of hen lysozyme (3SS-lysozyme) were prepared by replacing two Cys residues with Ala or Ser: C6S/C127A, C30A/C115A, C64A/C80A and C76A/C94A. The recombinant hen lysozyme was studied as the standard reference containing four authentic disulfide bridges and the extra N-terminal Met: the recombinant hen lysozyme containing the extra N-terminal. Folding rates were measured by monitoring the change in fluorescence intensity associated with tri- N-acetyl- d-glucosamine binding to the active site of refolded lysozyme. It was confirmed that the folding rate of the recombinant hen lysozyme containing the extra N-terminal was the same as that of wild-type lysozyme, and that the folding rate was little affected by the presence of tri- N-acetyl- d-glucosamine (triNAG). The folding rate of C64A/C80A was found to be the fastest and almost the same as that of the recombinant hen lysozyme containing the extra N-terminal, and that of C30A/C115A the second, and that of C6S/C127A the third. The folding rate of C76A/C94A was particularly slow. On the other hand, the unfolding rates which were measured in the presence of triNAG showed the dependence on the concentration of triNAG. The intrinsic unfolding rate in the absence of triNAG was determined by extrapolation. Also in the unfolding rate, C76A/C94A was markedly slower than the others. It was found from the analysis of binding constants of triNAG to C64A/C80A during the unfolding process that the active site of C64A/C80A partly unfolds already prior to the unfolding transition. On the basis of these kinetic data, we suggest that C64A/C80A folding transition can occur with leaving the loop region around SS3 (C64-C80) flexible, while cross-linking by SS4 (C76-C94) is important for the promotion of folding, because it is an indispensable constraint on the way towards the folding transition state.